Stature and Its Estimation Utilizing Arm Span Measurements in Male Adolescents from Federation of Bosnia and Herzegovina Entity in Bosnia and Herzegovina - Jovan Gardasevic; Faris Rasidagic; Dragan Krivokapic; Marin Corluka; Dusko Bjelica (Montenegrin Sports Academy, 2017)
The purpose of this study was to evaluate stature in males from the Federation of Bosnia and Herzegovina Entity in Bosnia and Herzegovina (hereinafter BH) as well as the relationship between arm span as an alternative to estimating stature, which varies in different ethnic and racial groups. The nature and scope of this study analyse 193 male students (aged 20.84±2.08) from the University of Sarajevo and University of Mostar. Anthropometric measurements were used in accordance with the protocol of the ISAK. Means and standard deviations were obtained. Statures and arm spans were compared using a t-test. The relation between arm span and stature were determined using simple correlation coefficients and a confidence interval of them of 95%. A linear regression analysis was then executed to examine the extent to which stature can be reliably predicted by arm span. The results have shown that males from the Federation of Bosnia and Herzegovina Entity are 183.84±6.41 cm tall and have an arm span of 185.65±7.55 cm. In comparison to other studies, the results of this one show the BH population to be one of the tallest nations in the world, perhaps the tallest one. Moreover, arm span surely predicts stature in males (61.6%). However, the estimation equations, which were obtained in Bosnian Herzegovinians from mentioned entity, are substantially different alike in the population from other entities, since arm span was not close to statures (1.81±1.14 cm more than the stature). This confirms the need for developing individual height models for this population.